Quality of life among the patients with ischemic heart disease attending the Cardiology clinic, Teaching hospital, Jaffna - Ashika, A.; Lakmina, E.A.T.S.; Abeyrathna, H.M.W.D.; Hansa, N.F.; Sujeeva, S.; Coonghe, P.A.D.; Kumaran, S.; Lakshman, P. (University of Jaffna, 2024)
Introduction and objective: Ischemic Heart Disease (IHD) is a global health challenge, causing significant mortality and morbidity across all age groups. Improving the Quality of Life (QoL), including physical, psychological, social, and environmental aspects, for IHD patients is an important aspect of management. This understanding can lead to tailored healthcare strategies and improved care for IHD patients, ultimately striving for better outcomes and well-being. This study aims to measure the quality of life and risk factors among patients with IHD attending the Cardiology Clinic, Teaching Hospital Jaffna. Methods: A hospital-based descriptive cross-sectional study was conducted between February 2022 and October 2023, involving 427 IHD patients, using systematic sampling. Data were collected using an interviewer-; administered questionnaire incorporated with MOS SF- 36 (Medical Outcome Study – Short Form). The study assessed various aspects of QoL including physical functioning, QoL limitations due to physical health, emotional well-being, energy/fatigue, and social functioning. Chi square test was used to assess the association between known risk factors and QoL. Results: Majority of the study participants were men (57.6%), aged above 55 years and Hindus (95.8%). Obesity was prevalent among 40% of the participants; 44%, 42.2%, 52.5% of the sample had diabetes mellitus, dyslipidemia and hypertension, respectively; 63.2 % experienced limitations in activities of daily living. No significant association was found between QoL and having diabetes mellitus (p value=0.88), hypertension (p value= 0.197), dyslipidemia (p value= 0.054), alcohol consumption (p value=0.58), and BMI ( p value= 0.74). However, QoL was found to be significantly associated with smoking (p value=0.02) and age (p value < 0.01). Conclusion and recommendations: QoL of patients with IHD is negatively associated with smoking and aging. These findings provide valuable insights into modifiable (smoking) and non-modifiable (age) risk factors that affect the QoL of patients with IHD and highlight the need to address and intervene with appropriate measures to improve the QoL of patients with IHD.
Keywords: Ischemic heart disease; Quality of life; Risk factors; Intervention